A heat-sensitive nutritional composition and a process for its steady-state treatment
Patent Information
- Application Number
- CN202611387923.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]然而,采用喷雾干燥预制微囊粉体时,微囊需先经历制囊干燥,随后在湿法制粒等工序中又会重新润湿、受剪切并再次干燥,可能增加被包埋物的重复受热以及囊壁再分散损伤
1.本发明采用钙离子部分交联、蛋白质酶促共价交联和改性纤维素非共价穿插相共同构建互穿网络壳层。钙离子交联用于初步定型并保留pH响应所需的游离羧基,蛋白质共价交联网络和改性纤维素穿插相用于分担剪切及干燥收缩应力,配合壳层厚度与微囊粒径的匹配,可提高制剂加工后的囊壁完整性和活性组分保留率。
Smart Images

Figure CN122893709A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of food processing technology, specifically relating to a heat-sensitive nutritional composition and its stabilization process. Background Technology
[0002] Heat-sensitive nutrients such as vitamin C, B vitamins, alpha-lipoic acid, reduced glutathione, and some bioactive peptides contain structures susceptible to the effects of heat, oxygen, or moisture. During wet granulation, drying, spray drying, tableting, or filling processes, shearing, heating, and oxygen mass transfer can cause oxidation, polymerization, or degradation of these nutrients, leading to a decrease in formulation content, color, or flavor stability. In addition to processing stability, nutrient microcapsules also need to inhibit premature release in the stomach and release nutrients promptly after entering the intestines. Therefore, how to balance formulation processing protection, gastric protection, and intestinal release within the same microcapsule system is a technical problem that needs to be solved in this field.
[0003] Existing technologies employ microencapsulation and cross-linking to improve the stability of sensitive components. For example, Chinese patent CN102106480A discloses a microcapsule of B vitamins and a method for preparing the microcapsule using spray drying. Gum arabic, maltodextrin, gelatin, and sucrose are used as wall materials, and the microcapsule powder is obtained through homogenization and spray drying to improve the stability of B vitamins. Chinese patent CN104313005B discloses a highly stable lactic acid bacteria microcapsule and its preparation method and application. First, calcium ions are used to form alginate capsules, and then transglutaminase is used to cross-link the proteins in the capsule wall to improve the mechanical stability of the bacterial-containing core capsules during continuous culture and inoculation. These methods, through wall material barrier and double cross-linking to enhance the capsule wall, provide a technical basis for the microencapsulation protection of sensitive components.
[0004] However, when using spray drying to pre-form microcapsule powder, the microcapsules must first undergo encapsulation drying, and then be re-wetted, sheared, and dried again in processes such as wet granulation. This may increase repeated heating of the encapsulated material and damage to the capsule wall due to redispersion. For pH-sensitive polysaccharides with calcium ion crosslinking, while increasing the degree of crosslinking is beneficial for enhancing capsule wall strength, it reduces the number of free carboxyl groups that can dissociate in neutral media, thus affecting swelling and release in intestinal fluid. Simply reducing the degree of calcium crosslinking is insufficient to meet the capsule wall strength requirements of the granulation and drying processes. Furthermore, existing technologies have not systematically defined the relationship between the degree of ion crosslinking, protein covalent crosslinking network, modified cellulose intercalation phase, and shell thickness and microcapsule particle size. Therefore, there is still a need for a heat-sensitive nutritional composition that can reduce pre-drying and redispersion steps while taking into account processing stability, gastric protection, and intestinal release. Summary of the Invention
[0005] This invention provides a thermosensitive nutritional composition and its stabilization process, which balances the stability of thermosensitive nutritional components during formulation processing with gastric protection and intestinal release properties, and reduces the encapsulation drying and redispersibility steps in the pre-formulated microcapsule route. The "stabilization process" referred to in this application means completing the initial microcapsule formation, ionic cross-linking, enzymatic covalent cross-linking, and enzyme inactivation during the liquid phase stage of the formulation, so that the microcapsules form a stable interpenetrating network shell before being incorporated into subsequent formulation processes, and does not refer to the material being in a state of thermodynamic equilibrium.
[0006] According to one aspect of the present invention, a thermosensitive nutritional composition is provided, comprising core-shell structured microcapsules. The microcapsules comprise a core material and an interpenetrating network shell covering the periphery of the core material. The core material comprises thermosensitive nutritional components and antioxidants. The interpenetrating network shell is composed of pH-sensitive polysaccharides, edible plant proteins, and modified cellulose. The pH-sensitive polysaccharides are cross-linked with calcium ions to form an ionic cross-linked network continuously distributed along the periphery of the core material. The edible plant proteins are catalyzed by transglutaminase to form a covalently cross-linked network distributed along the capsule wall interface defined by the ionic cross-linked network. The two types of cross-linked networks interpenetrate each other, and the modified cellulose is interpenetrated and fixed between the two types of cross-linked networks to form a rigid framework.
[0007] By weight, the pH-sensitive polysaccharide is 30-60 parts, the edible plant protein is 20-50 parts, and the modified cellulose is 5-20 parts; the mass of the modified cellulose is 5%-20% of the total mass of the pH-sensitive polysaccharide, edible plant protein, and modified cellulose. The total mass ratio of the thermosensitive nutrient components and antioxidants to the total mass of the above-mentioned compound carrier is 1:1 to 1:4, and the volume average particle size D[4,3] of the microcapsules is 5-100 μm.
[0008] The cross-linking state and geometry of the interpenetrating network shell are as follows.
[0009] (1) Calcium ions partially crosslink pH-sensitive polysaccharides while retaining free carboxyl groups. After ionic crosslinking, the molar fraction of free carboxyl groups in the pH-sensitive polysaccharides in the interpenetrating network shell is 50%–80%. The retained free carboxyl groups are used to maintain the dissociation and swelling capacity of the shell in neutral media. The covalent crosslinking network formed by edible plant protein and the modified cellulose interpenetrating phase are used to supplement the shell wall strength, thereby reducing the adverse effect of simply increasing the degree of calcium ion crosslinking on intestinal fluid release.
[0010] (2) Matching of shell thickness and microcapsule particle size. The ratio of the thickness of the interpenetrating network shell to the volume average particle size of the microcapsules is 0.02 to 0.10. When this ratio is less than 0.02, the shell is insufficient to withstand the granulation shear and drying shrinkage stress, the integrity rate of the capsule wall decreases significantly and obvious leakage occurs in simulated gastric fluid; when this ratio is greater than 0.10, the shell is difficult to complete swelling and dissociation within 45 min in simulated intestinal fluid, and the intestinal release rate decreases significantly.
[0011] (3) The covalent cross-linked protein network is radially distributed along the shell. The covalent cross-linked network is relatively concentrated on the outer side and relatively loose on the inner side. To quantitatively characterize this distribution, parallel analytical samples with the same formulation and process as the microcapsules to be tested were prepared. Edible plant protein labeled with fluorescein isothiocyanate and unlabeled edible plant protein were mixed at a mass ratio of 1:19 and fed into the microcapsules. Confocal imaging was performed on the equatorial surface of the cross-linked microcapsules. The ratio of the average fluorescence intensity of the labeled protein in the outer half-thickness region to the inner half-thickness region of the shell was defined as the radial protein network distribution gradient value, which is 1.5 to 3.0. This characterization value is used to reflect the relative radial distribution of the protein network in the shell and does not represent the absolute concentration of isopeptide bonds. The ionic cross-linked network formed first shapes the interface of the primary capsule wall, which is conducive to the gradual formation of subsequent protein covalent cross-links along the capsule wall region. The relatively concentrated protein network on the outer side is conducive to withstanding external shear and drying shrinkage stress, while the relatively loose region on the inner side is conducive to the swelling and dissociation of the shell in intestinal fluid.
[0012] Furthermore, ionic cross-linking utilizes one or more of calcium lactate, calcium chloride, and calcium gluconate, with the amount of calcium ions used being 1.2%–5.0% of the mass of the pH-sensitive polysaccharide, and the molar ratio of calcium ions to the dissociable carboxyl groups in the pH-sensitive polysaccharide being 0.10–0.25. Enzymatic covalent cross-linking uses transglutaminase, with an addition amount of 5–30 U per gram of edible plant protein, based on enzyme activity. Transglutaminase catalyzes the formation of ε-(γ-glutamyl)-lysine isopeptide bonds between edible plant protein molecules. Since the content of dissociable carboxyl groups per unit mass varies among different pH-sensitive polysaccharides, the percentage of calcium ions used should simultaneously satisfy the aforementioned molar ratio and the molar fraction of free carboxyl groups. Ionic cross-linking is performed prior to enzymatic covalent cross-linking, allowing the primary capsule wall to be first positioned and shaped by ionic cross-linking before forming a protein covalent cross-linked network.
[0013] Further, the pH-sensitive polysaccharide is selected from one or more of sodium alginate, low-ester pectin, and gellan gum, wherein the degree of esterification of low-ester pectin is not higher than 45%; the edible plant protein is selected from one or two of soy protein isolate and pea protein, wherein the two proteins have good dispersibility in an aqueous phase with pH 3.5–4.5 and contain sufficient glutamine and lysine residues, and can serve as substrates for glutamine transaminase; the modified cellulose is selected from one or more of sodium carboxymethyl cellulose, hydroxypropyl methylcellulose, and colloidal microcrystalline cellulose. The heat-sensitive nutrient component can be selected from one or more of vitamin C and its salts or esters, B vitamins, vitamin A, vitamin D, vitamin E, α-lipoic acid, reduced glutathione, collagen peptides, soy peptides, coenzyme Q10, lutein, and lycopene. The antioxidant protectant can be selected from one or more of lecithin, vitamin E succinate, ascorbyl palmitate, rosemary extract, and tea polyphenols, and its amount is 2%–15% of the mass of the heat-sensitive nutrient component. Water-soluble heat-sensitive nutrients are dispersed in an aqueous medium to form the core material internal phase, while fat-soluble heat-sensitive nutrients are dispersed in edible oils to form the core material internal phase.
[0014] Furthermore, the modified cellulose exists as a non-covalent interpenetrating phase in the interpenetrating network shell. Its molecular chains do not contain glutamine and lysine residues, and therefore do not participate in the covalent cross-linking of proteins catalyzed by glutamine transaminase. It is fixed between the two types of cross-linked networks through segment entanglement and hydrogen bonding. The modified cellulose is water-soluble modified cellulose or colloidal microcrystalline cellulose; the viscosity of the water-soluble modified cellulose measured at 20°C in a 1% aqueous solution is not less than 500 mPa·s, and the average particle size of the colloidal microcrystalline cellulose is not greater than 0.5 μm. When the amount of modified cellulose is less than 5% of the total mass of the compound carrier, the shell lacks a stress-sharing phase during drying shrinkage; when the amount is more than 20% of the total mass of the compound carrier, the interpenetrating phase occupies more network gaps, which may limit the swelling and dissociation of the shell in a neutral medium.
[0015] Furthermore, trehalose and / or isomaltooligosaccharide can be distributed as pore-forming components in the interpenetrating network shell, with the mass of the pore-forming components being 5%–15% of the total mass of pH-sensitive polysaccharides, edible plant proteins, and modified cellulose. In a dry state, the pore-forming components fill the gaps in the shell network, reducing the tendency for the shell to crack due to water loss and shrinkage. Upon entering a medium with pH 6.8, the pore-forming components dissolve and form microporous channels, thereby shortening the core material release time. A hydrophobic anti-adhesion layer composed of zein particles, with an average particle size of 100–400 nm, can also be attached to the outer surface of the microcapsules. The amount of zein particles is 3%–10% of the mass of the compound carrier, used to reduce the adhesion and aggregation of microcapsules during concentration, granulation, and drying processes.
[0016] This invention also provides a thermosensitive nutritional composition formulation, comprising the above-mentioned thermosensitive nutritional composition and food excipients, in the form of tablets, granules, hard capsules, or soft capsules. When measured using the paddle method under conditions of a medium volume of 900 mL, a temperature of 37 ± 0.5 °C, and a rotation speed of 100 r / min, the cumulative release rate of the core material after incubation in simulated gastric fluid at pH 1.2 for 2 h is not higher than 8%, and the cumulative release rate of the core material after transferring the microcapsules into simulated intestinal fluid at pH 6.8 for 45 min is not lower than 90%.
[0017] The beneficial effects of this invention are as follows: 1. This invention employs a combination of calcium ion partial crosslinking, protein enzymatic covalent crosslinking, and a modified cellulose non-covalent interpenetrating phase to construct an interpenetrating network shell. Calcium ion crosslinking is used for initial shaping and to retain the free carboxyl groups required for pH response. The protein covalent crosslinking network and the modified cellulose interpenetrating phase are used to share shear and drying shrinkage stress. Combined with the matching of shell thickness and microcapsule particle size, this improves the integrity of the capsule wall and the retention rate of active components after formulation processing.
[0018] 2. This invention utilizes the network contraction of pH-sensitive polysaccharides in the gastric acid environment and their dissociation and swelling in the neutral environment, combined with the dissolution of pore-regulating components in intestinal fluid, so that the microcapsules can maintain low release in simulated gastric fluid and release more quickly after being transferred to simulated intestinal fluid, thus taking into account both gastric protection and intestinal release.
[0019] 3. In this invention, the initial microcapsule forming and sequential cross-linking are completed in the liquid phase process of the formulation. The cross-linked microcapsule suspension can be fed into the granulation, filling or spray drying process without separation, washing and pre-drying, which reduces the encapsulation drying and redispersion steps in the pre-made microcapsule route and reduces repeated heating of heat-sensitive nutrients and damage to the capsule wall due to redispersion.
[0020] 4. The encapsulation and cross-linking process of the present invention adopts a food-grade aqueous phase system, and water-soluble or fat-soluble heat-sensitive nutrient components can be processed through the corresponding core material internal phase; optional zein particles are pre-prepared using edible ethanol, and the ethanol is removed before adding the microcapsule suspension, which facilitates adaptation to various dosage forms such as tablets, granules, hard capsules and soft capsules. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the stabilization process flow of the present invention; Figure 2 Comparison of the morphology of microcapsules after cross-linking curing, granulation and drying followed by rehydration, and after regranulation of pre-made microcapsules; Figure 3 Comparison of surface morphology of double cross-linked microcapsules and single ion cross-linked microcapsules after granulation and drying; Figure 4A comparison of the characteristic peaks of the Fourier transform infrared spectra of the composite carrier physical mixture, the ion-crosslinked shell, and the double-crosslinked shell; Figure 5 This is a laser particle size distribution diagram of the microcapsules in Example 1; Figure 6 This is a comparison chart of the capsule wall integrity rate and product activity retention rate in each group of test example 1; Figure 7 A comparison chart of the cumulative release rates of simulated gastric juice and simulated intestinal juice in representative groups of Test Example 2; Figure 8 The graph shows the change in the retention rate of the active component during the accelerated stability test of Example 3. Detailed Implementation
[0022] The present invention will be further described below with reference to the accompanying drawings and embodiments. The following embodiments are used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention; the structural dimensions in the drawings are for illustration only and do not represent actual proportions.
[0023] Raw material description: Vitamin C, food grade, purity not less than 99%; Alpha-lipoic acid, food grade, purity not less than 98%; Reduced glutathione, food grade, purity not less than 98%.
[0024] Sodium alginate, food grade, with a viscosity of 200–400 mPa·s at 20°C in a 1% aqueous solution; sodium uronic acid repeat molar mass is calculated as 198.1 g / mol; low-ester pectin, food grade, with an esterification degree not exceeding 45%, and the actual measured esterification degree is 45%; gellan gum, food grade, low acyl type.
[0025] Soy protein isolate, food grade, with a protein content of not less than 90%; Pea protein, food grade, with a protein content of not less than 80%.
[0026] Sodium carboxymethyl cellulose, food grade, degree of substitution 0.7–0.9, viscosity of 1% aqueous solution at 20℃ is 800–1200 mPa·s; hydroxypropyl methyl cellulose, food grade, methoxy content 19%–24%, viscosity of 1% aqueous solution at 20℃ is 500–800 mPa·s; colloidal microcrystalline cellulose, food grade, average particle size not greater than 0.5 μm.
[0027] Transglutaminase, an edible-grade enzyme preparation, has a labeled enzyme activity of 100 U / g. The actual amount added should be calculated based on the labeled enzyme activity. Calcium lactate (pentahydrate, calcium content 13.0%), calcium gluconate (monohydrate, calcium content 8.9%), and calcium chloride (dihydrate, calcium content 27.3%) are all edible-grade. The actual amount added should be calculated based on the labeled or measured calcium content of the raw materials.
[0028] Soy lecithin, food grade, with acetone-insoluble matter not less than 60%; Vitamin E succinate and rosemary extract are both food grade, with the rosemary extract containing not less than 5% caryopsisic acid; Tea polyphenols, food grade, with a tea polyphenol content not less than 98%; Medium-chain triglycerides are food grade C8 / C10 type.
[0029] Trehalose, food grade, with a purity of not less than 98%; Isomaltooligosaccharide, food grade, with an isomaltooligosaccharide content of not less than 90% in the solids.
[0030] Corn gliadin, food grade, with a protein content of not less than 88%; food-grade ethanol, with a concentration and volume fraction of 95%.
[0031] Microcrystalline cellulose (powder grade, average particle size 50-100μm), lactose (100 mesh), maltodextrin (DE value 15-20), chitosan (degree of deacetylation not less than 90%), gelatin (bloom strength 200), glycerol, anhydrous citric acid and magnesium stearate are all food grade or meet the requirements for food additives.
[0032] Pepsin (1:3000) and trypsin (1:100) were biochemical reagents; fluorescein isothiocyanate, anhydrous sodium carbonate, sodium bicarbonate, sodium hydroxide, hydrochloric acid, phosphoric acid, potassium dihydrogen phosphate, acetonitrile, and methanol were of analytical or chromatographic grade; polysorbate 80 was food grade. Purified water was used in both the examples and comparative examples.
[0033] Main instruments and equipment: High-shear dispersion homogenizer (speed 0~20000r / min); high-pressure homogenizer (0~60MPa); gelling tank (with stirring, temperature control accuracy ±0.5℃); high-shear wet granulation machine; automatic soft capsule spinning machine; drying equipment; drug dissolution tester (paddle method); constant temperature and humidity chamber (40℃, relative humidity 75%).
[0034] Detection and characterization methods: The centrifugation, washing, filtration, dialysis, and media transfer operations mentioned in this section are only used for analysis sampling or detection and are not production steps in the stabilization process.
[0035] 1. Volume average particle size. The suspension sample was diluted with purified water to an opacity of 10%–15%, and measured using a laser diffractometer. The values of D[4,3] and D were recorded. 50 D 10 and D 90 Span according to (D) 90 -D 10 ) / D 50 Calculate and perform three parallel measurements, then take the arithmetic mean.
[0036] 2. Interpenetrating network shell thickness and its ratio to particle size. Parallel analytical samples with the same formulation and process as the microcapsules to be tested were prepared. Edible plant protein was pre-labeled with fluorescein isothiocyanate: 0.5 mg of fluorescein isothiocyanate was added per gram of protein, and the mixture was reacted in carbonate buffer at pH 9.0 at 4°C for 12 h. After dialysis to remove free dye, the sample was used. Labeled and unlabeled proteins were mixed at a mass ratio of 1:19. A microcapsule sample in suspension was dropped onto a glass slide, and the equatorial plane of the microcapsule was optically sectioned under a confocal laser scanning microscope. The radial distance between the inner and outer contours of the fluorescent shell was measured. At least 50 microcapsules were randomly measured, and the arithmetic mean was taken as the shell thickness. The ratio of the shell thickness to the volume average particle size D[4,3] of the same batch of samples was the shell thickness ratio.
[0037] 3. Radial Protein Network Distribution Gradient Value. From the confocal images of the parallel samples analyzed above, the fluorescence intensity distribution curve of the shell was extracted radially along the microcapsule. The shell was divided into an outer half and an inner half along the thickness direction. The average fluorescence intensity of the labeled protein in each half was calculated. The ratio of the average fluorescence intensity of the outer half to the average fluorescence intensity of the inner half was used as the radial protein network distribution gradient value. This value characterizes the relative distribution of the cross-linked protein network radially in the shell and does not represent the absolute concentration of isopeptide bonds. At least 30 microcapsules were randomly measured in each group, and the arithmetic mean was taken.
[0038] 4. Mole fraction of free carboxyl groups. The calcium occupancy reduction method was used for determination. The specific steps were as follows: (a) Calculate the total mole fraction of dissociable carboxyl groups based on the amount of pH-sensitive polysaccharide fed and the corresponding content of dissociable carboxyl groups per unit mass; (b) Take the cross-linked microcapsule suspension, centrifuge and wash it three times with purified water at 3000 r / min to remove unbound free calcium ions, take the precipitate and digest it with 0.1 mol / L hydrochloric acid, and determine the mass of bound calcium in the shell layer by flame atomic absorption spectrophotometry and convert it into the mole fraction of bound calcium.
[0039] Based on the assumption that each mole of calcium ion occupies 2 moles of carboxyl groups, the mole fraction of free carboxyl groups is calculated using the following formula: Free carboxyl mole fraction = [n(COOH) - 2n(Ca)] / n(COOH) × 100% In the formula, n(COOH) is the total molar amount of dissociable carboxyl groups in the pH-sensitive polysaccharide, and n(Ca) is the molar amount of bound calcium in the interpenetrating network shell. The determination was performed in triplicate, and the arithmetic mean was taken.
[0040] As a verification method, the washed precipitate can also be potentiometrically titrated with a 0.05 mol / L sodium hydroxide standard solution, and the molar amount of free carboxyl groups can be determined based on the amount of alkali consumed; the relative deviation of the results obtained by the two methods in each embodiment of the present invention does not exceed 5%.
[0041] 5. Molar ratio of calcium ions to dissociable carboxyl groups. Calculated as n(Ca input) / n(COOH), where n(Ca input) is converted from the amount of calcium salt added and its calcium content.
[0042] 6. Preparation of simulated gastric and intestinal fluids. Simulated gastric fluid: Dissolve 16.4 mL of dilute hydrochloric acid in approximately 800 mL of purified water and 10 g of pepsin. Shake well and dilute with purified water to 1000 mL. The measured pH is 1.2. Simulated intestinal fluid: Dissolve 6.8 g of potassium dihydrogen phosphate in 500 mL of purified water. Adjust the pH to 6.8 with 0.1 mol / L sodium hydroxide solution. Separately, dissolve 10 g of pancreatin in an appropriate amount of purified water. Mix the two solutions and dilute with purified water to 1000 mL.
[0043] 7. Cumulative Release Rate of Core Material. The paddle method was used, with a medium volume of 900 mL, a temperature of 37 ± 0.5℃, and a rotation speed of 100 r / min. 5 mL samples were taken periodically, and 5 mL of isothermal medium was added. The sample was filtered through a 0.45 μm microporous membrane before determining the content of the active component. The adsorption loss of the active component by the filter membrane was verified by a spiked recovery test to be no higher than 2%. The cumulative release rate of the core material was calculated as "mass of released active component in the release medium / total mass of active component in the sample × 100%", with a cumulative correction for media loss due to sampling.
[0044] 8. Determination of active ingredient content. Vitamin C was determined by 2,6-dichlorophenolindophenol titration. α-Lipoic acid was determined by high-performance liquid chromatography (HPLC): a C18 column (250 mm × 4.6 mm, 5 μm), a mobile phase of acetonitrile-0.1% phosphoric acid aqueous solution (55:45, v / v), a flow rate of 1.0 mL / min, a column temperature of 30℃, and a detection wavelength of 330 nm. Reduced glutathione was determined by HPLC: a C18 column (250 mm × 4.6 mm, 5 μm), a mobile phase of 0.05 mol / L phosphate buffer (pH 3.0)-methanol (95:5, v / v), a flow rate of 1.0 mL / min, a column temperature of 30℃, and a detection wavelength of 210 nm. All the above HPLC methods were validated for specificity, linearity, precision, and recovery. The recoveries were 98%–102%, and the relative standard deviations were no greater than 2.0%.
[0045] 9. Solid content. Take about 2g of the suspension sample and dry it in a drying oven at 105℃ until constant weight. Calculate the solid content based on the ratio of the mass before and after drying. Perform the determination in three parallel trials and take the average value.
[0046] Example 1 like Figure 1As shown, in step S1, preparation of the core material internal phase: 60g of vitamin C and 6g of soybean lecithin were added to 240g of purified water and stirred at 30℃ and 300r / min for 15min until uniformly dispersed, yielding 306g of the core material internal phase. The mass of the core material functional substance was 66g, of which the amount of soybean lecithin was 10% of the mass of vitamin C.
[0047] Step S2, preparation of the composite carrier solution: Add 45g of sodium alginate, 35g of soy protein isolate, and 12g of sodium carboxymethyl cellulose to 1800g of purified water. Stir at 50℃ and 400r / min for 60min until homogeneous, then cool to 30℃ to obtain a composite carrier solution with a mass concentration of approximately 4.9% (92 / 1892=4.86%). The mass ratio of the three composite carriers is 45:35:12, with a total mass of 92g, of which sodium carboxymethyl cellulose accounts for 13.0% of the total mass of the composite carriers; the mass ratio of the core material functional substance to the composite carrier is approximately 1:1.4 (66:92=1:1.39).
[0048] Step S3, in-situ embedding initial formation: The inner phase of the core material is added to the composite carrier solution and dispersed at a high speed of 10000 r / min for 5 min. The pH of the system is adjusted to 4.0 at 30℃ using a 10% citric acid solution (approximately 12 g of citric acid solution, controlled by a pH meter endpoint). The mixture is then stirred at 300 r / min for 20 min to allow the soy protein isolate and sodium alginate to aggregate around the core material dispersion micro-region and form the initial capsule wall, resulting in the initial microcapsule dispersion. The particle size distribution (D[4,3]) of the initial microcapsule dispersion was determined to be 39.2 μm by laser diffraction particle size analyzer.
[0049] Step S4, sequential crosslinking and curing: First stage (low-temperature ionic crosslinking): The system was cooled to 25℃, and 138.5g of a 10% calcium lactate solution was added (containing 13.85g of calcium lactate pentahydrate; based on a calcium content of 13.0%, the mass of calcium ions is 1.80g, which is 4.0% of the mass of sodium alginate). Ionic crosslinking was completed by stirring at 300r / min for 15min. The total molar amount of dissociable carboxyl groups in 45g of sodium alginate is 45×5.05=227.2mmol, and the molar amount of calcium ions is 1.80 / 40.08=44.9mmol. The molar ratio of calcium ions to dissociable carboxyl groups is 0.198. Based on the calculation that each mole of calcium ion occupies 2 moles of carboxyl groups, the molar fraction of free carboxyl groups in the shell is (227.2-2×44.9) / 227.2×100%=60.5%, which was actually measured to be 60.5% using the calcium occupancy conversion method.
[0050] The second stage (temperature-increased enzymatic covalent cross-linking): Within 10 minutes after the completion of ionic cross-linking, 5.25 g of transglutaminase (labeled enzyme activity 100 U / g, i.e., 525 U, the amount of enzyme activity used is 15 U / g of soybean protein isolate) was added. Simultaneously, the system was heated to 38℃ and reacted at 38℃ and 200 r / min for 40 minutes. Then, the temperature was increased to 70℃ and held for 5 minutes to inactivate the enzyme, followed by cooling to 30℃ to obtain a cross-linked microcapsule suspension. At this point, the total mass of the system was approximately 2354 g (306 g of core material internal phase, 1892 g of compound carrier solution, approximately 12 g of citric acid solution, 138.5 g of calcium lactate solution, and 5.25 g of transglutaminase), of which approximately 178 g was non-volatile matter, and the measured solid content was 7.6%.
[0051] The microcapsule diameter (D[4,3]) was determined to be 37.4 μm by laser diffraction particle size analyzer. 50 It is 35.1 μm, D 10 It is 12.6 μm, D 90 The particle size distribution is 68.3 μm with a span of 1.59. Figure 5 Confocal laser scanning microscopy revealed a shell thickness of 1.8 μm, a shell-to-thickness ratio of 1.8 / 37.4 = 0.048, and a radial protein network distribution gradient of 1.9. The morphology after cross-linking and curing is also shown. Figure 2 (a) in the middle.
[0052] Step S5, connected with subsequent formulation processes: The cross-linked microcapsule suspension is concentrated in a vacuum film at 45°C and 5 kPa absolute pressure to a solid content of about 35%, yielding a suspension of about 509 g (of which about 178 g is non-volatile matter, including 66 g of core material functional substances, 92 g of compound carrier, 13.85 g of calcium lactate, 5.25 g of transglutaminase and about 1.2 g of citric acid). Microcapsule separation, washing and pre-drying are not performed.
[0053] 200g of microcrystalline cellulose and 290g of lactose were mixed to obtain 490g of excipient mixture powder, which was then placed in a high-shear wet granulator. A multi-stage slurry addition-intermediate drying method was used, with approximately 102g (20.8% of the excipient mixture powder mass) added in five separate additions. After each addition, the mixture was formed into a soft mass for 3 minutes, granulated through a 24-mesh sieve, and then intermediate-dried for 15 minutes at an inlet air temperature of 60℃. After the final slurry addition, the mixture was dried at 60℃ for 40 minutes until the granule moisture content was no higher than 3.0% and the granule bed temperature did not exceed 45℃. Granulation was passed through a 20-mesh sieve, yielding approximately 668g of granules. 3.34g of magnesium stearate (0.5% of the granule mass) was added and mixed for 5 minutes. The mixture was then pressed into tablets using a Φ10mm shallow concave die, with each tablet weighing 0.80g and having a hardness of 70–90N. This yielded vitamin C microcapsules, each containing approximately 71mg of vitamin C (60 / 671.3 × 0.80g = 71.5mg). The morphology of the rehydrated microcapsules after granulation and drying is shown in the image. Figure 2 (b) in the middle.
[0054] Fourier transform infrared spectroscopy was performed on the shell material of Example 1, and the characteristic peak comparison results are shown. Figure 4 Compared to physical mixtures with composite carriers, COO after ionic crosslinking... - The asymmetric stretching vibration peak is 1610 cm⁻¹ -1 Moved to 1595cm -1 1425cm -1 The enhanced symmetric stretching vibration peaks nearby indicate coordination between calcium ions and the carboxyl groups of sodium alginate; the amide I band reaches 1652 cm⁻¹ after double crosslinking. -1 and amide II band 1543cm -1 The enhancement indicates that glutamine transaminase catalyzes the formation of ε-(γ-glutamyl) lysine isopeptide bonds in soy protein isolate.
[0055] Example 2 The difference from Example 1 is that in step S1, 50g of α-lipoic acid and 5g of vitamin E succinate are dispersed in 55g of medium-chain triglycerides at 45°C and stirred for 20min to form 110g of oily core material internal phase, the mass of core material functional material is 55g, and the amount of vitamin E succinate is 10% of the mass of α-lipoic acid.
[0056] In step S2, the composite carrier consists of 60g of low-ester pectin, 40g of pea protein, and 10g of hydroxypropyl methylcellulose, dissolved or dispersed in 1300g of purified water. The mass concentration of the composite carrier solution is approximately 7.8% (110 / 1410=7.80%), and the mass ratio of the three components is 30:20:5, with a total mass of 110g. Hydroxypropyl methylcellulose accounts for 9.1% of the total mass of the composite carrier. The mass ratio of the core material functional substance to the composite carrier is 1:2.
[0057] In step S3, an O / W type dispersion system was formed by shearing and dispersing at 8000 r / min for 5 min. The pH was adjusted to 4.5 at 25℃, and the D[4,3] of the resulting initial microcapsule dispersion was 98 μm.
[0058] In step S4, the system is cooled to 22°C. 13.48g of calcium gluconate monohydrate (calculated based on its calcium content of 8.9%, the mass of calcium ions is 1.20g, which is 2.0% of the mass of low-ester pectin) is added in three batches in solid powder form and stirred for 20 minutes until completely dissolved. The mass concentration of calcium gluconate in the system is about 0.9%, which is lower than its solubility in purified water at 22°C. The degree of esterification of low-ester pectin is 45%, and the average molar mass of repeating units is 0.45×190.2+0.55×176.1=182.4g / mol. Each gram contains 0.55 / 182.4=3.02mmol of dissociable carboxyl groups. The total molar amount of dissociable carboxyl groups in 60g of low-ester pectin is 180.9mmol. The molar amount of calcium ions is 1.20 / 40.08=29.9mmol. The molar ratio of calcium ions to dissociable carboxyl groups is 0.166. The molar fraction of free carboxyl groups in the shell is (180.9-2×29.9) / 180.9×100%=66.9%.
[0059] In step S4, the second stage, 2.00 g of transglutaminase (200 U, enzyme activity equivalent to 5 U / g of pea protein) was added within 10 min after the ionic cross-linking was completed. Simultaneously, the temperature was raised to 30℃ and reacted for 60 min, followed by enzyme inactivation at 65℃ for 10 min. The resulting microcapsules D[4,3] had a diameter of 95 μm, a shell thickness of 7.0 μm, a shell-to-thickness ratio of 7.0 / 95 = 0.074, and a radial protein network distribution gradient of 2.1.
[0060] In step S5, the cross-linked microcapsule suspension is concentrated under vacuum at 45°C and 5 kPa to a solid content of approximately 30%, yielding approximately 788 g of suspension (including approximately 236 g of non-volatile matter, comprising 110 g of the core material internal phase, 110 g of the compounded carrier, 13.48 g of calcium gluconate, 2.00 g of transglutaminase, and approximately 0.8 g of citric acid). 250 g of medium-chain triglycerides are added to the concentrated suspension, and the mixture is homogenized at 40°C and 200 r / min. Subsequently, the mixture is further dehydrated under reduced pressure at 45°C and 3 kPa until the water content is no higher than 5% (measured at 4.2%), yielding approximately 508 g of oil-phase suspension containing the contents (approximately 486 g of non-volatile matter and approximately 21 g of residual water), of which the mass fraction of α-lipoic acid is approximately 9.8%. A capsule shell solution was prepared by mixing gelatin, glycerin, and purified water in a mass ratio of 1:0.4:0.8. The solution was then filled using an automatic soft capsule rotary molding machine with a gelatin strip thickness of 0.8 mm. The capsule shell temperature was controlled to not exceed 60°C. The capsules were then dried in a rotary drum at 25°C and 20% relative humidity for 24 hours to obtain α-lipoic acid microcapsules. Each capsule contained 0.60 g of contents and approximately 59 mg of α-lipoic acid.
[0061] Example 3 The difference from Example 1 is that in step S1, 60g of reduced glutathione and 3g of rosemary extract are dissolved or dispersed in 240g of purified water to form 303g of aqueous core material internal phase, the mass of core material functional substance is 63g, and the amount of rosemary extract used is 5% of the mass of reduced glutathione.
[0062] In step S2, the composite carrier consists of 116g sodium alginate, 97g soy protein isolate, and 39g sodium carboxymethyl cellulose, dissolved or dispersed in 12000g purified water. The mass concentration of the composite carrier solution is approximately 2.1% (252 / 12252=2.06%), and the mass ratio of the three components is approximately 60:50:20, with a total mass of 252g. Among them, sodium carboxymethyl cellulose accounts for 15.5% of the total mass of the composite carrier. The mass ratio of the core material functional substance to the composite carrier is 1:4.
[0063] In step S3, the microcapsule dispersion was homogenized twice under high pressure at 35 MPa and the pH was adjusted to 3.5 at 40 °C (approximately 60 g of citric acid solution was used). The resulting microcapsule dispersion had a D[4,3] of 6.4 μm.
[0064] In step S4, the system was cooled to 28°C, and 212.4 g of a 10% calcium chloride solution (containing 21.24 g of calcium chloride dihydrate; based on a calcium content of 27.3%, the mass of calcium ions was 5.80 g, which is 5.0% of the mass of sodium alginate) was added. The mixture was stirred for 15 min. The total molar amount of dissociable carboxyl groups in 116 g of sodium alginate was 585.6 mmol, and the molar amount of calcium ions was 5.80 / 40.08 = 144.7 mmol. The molar ratio of calcium ions to dissociable carboxyl groups was 0.247, and the molar fraction of free carboxyl groups in the shell was (585.6 - 2 × 144.7) / 585.6 × 100% = 50.6%.
[0065] In step S4, the second stage, 29.10 g of transglutaminase (i.e., 2910 U, enzyme activity equivalent to 30 U / g of soybean protein isolate) was added within 10 min after the ionic cross-linking was completed. Simultaneously, the temperature was raised to 45℃ and reacted for 20 min, followed by enzyme inactivation at 75℃ for 3 min. The resulting microcapsules D[4,3] had a diameter of 6.0 μm, a shell thickness of 0.40 μm, a shell-to-thickness ratio of 0.40 / 6.0 = 0.067, and a radial protein network distribution gradient of 1.7.
[0066] In step S5, the cross-linked microcapsule suspension is concentrated under vacuum at 45°C and 5 kPa to a solid content of approximately 15%, yielding approximately 2476 g of suspension (including approximately 371 g of non-volatile matter, comprising 63 g of core material functional substances, 252 g of compound carrier, 21.24 g of calcium chloride, 29.10 g of transglutaminase, and approximately 6 g of citric acid). 371 g of maltodextrin is added to the concentrated suspension and stirred until completely dissolved, yielding approximately 2847 g of feed liquid with a solid content of approximately 26%. This is directly fed into a drying device for drying, with the inlet air temperature controlled at 150°C, yielding approximately 690 g of granular powder (yield approximately 93%). After granulation and passing through a 20-mesh sieve, the powder is packaged into 2.0 g bags to obtain glutathione microcapsule granules, each bag containing approximately 162 mg of reduced glutathione.
[0067] Example 4 The difference from Example 1 is that in step S2, 10g of trehalose was added to the compound carrier solution. The mass of trehalose was 10.9% of the total mass of the compound carrier, and it was distributed in the interpenetrating network gaps during the coagulation and cross-linking process. In step S5, approximately 538g of concentrated suspension (approximately 188g of non-volatile matter) was added, along with 490g of excipient powder in five additions, each time approximately 108g (22.0% of the mass of the excipient powder), resulting in approximately 678g of granules. 3.39g of magnesium stearate was added, resulting in a tablet weight of 0.80g and each tablet containing approximately 70mg of vitamin C. The remaining raw materials and process parameters were the same as in Example 1. The resulting microcapsules had a diameter D[4,3] of 38.0μm, a shell thickness of 1.9μm, a shell-to-thickness ratio of 0.050, a radial protein network distribution gradient of 1.9, and a free carboxyl molar fraction of 60.4%.
[0068] Example 5 The difference from Example 4 is that: after inactivating the enzyme and cooling to 30°C in step S4, 92 mL of a 5% (w / v) zein particle dispersion (containing 4.6 g of zein particles, the amount added is 5.0% of the mass of the compound carrier) is added to the cross-linked microcapsule suspension, and the mixture is stirred and adsorbed at 30°C and 200 r / min for 20 min to form a hydrophobic anti-adhesion layer on the outer surface of the microcapsule.
[0069] The zein particle dispersion was prepared in advance using the edible ethanol antisolvent method: 5g of zein was dissolved in 100mL of 70% edible ethanol, and injected into 400mL of purified water at a rate of 10mL / min while stirring at 500r / min. Then, the ethanol was removed by rotary evaporation at 45℃ and 8kPa absolute pressure until the mass fraction of residual ethanol was not higher than 0.5%. Purified water was added to make up the volume to 100mL, resulting in a zein particle dispersion with a mass volume concentration of 5%. The measured average particle size was 200nm, the polydispersity index was 0.18, and the zeta potential was -28mV.
[0070] In step S5, approximately 551g of concentrated suspension (including approximately 193g of non-volatile matter) was added, along with 490g of excipient mixture powder in five additions, each time approximately 110g (22.5% of the mass of the excipient mixture powder), yielding approximately 683g of granules. 3.41g of magnesium stearate was added, resulting in a tablet weight of 0.80g and each tablet containing approximately 70mg of vitamin C. The resulting microcapsules D[4,3] had a diameter of 38.8μm, a shell thickness of 1.9μm, a shell-to-thickness ratio of 0.049, a radial protein network distribution gradient of 2.0, and a free carboxyl molar fraction of 60.5% in the shell.
[0071] Example 6 The difference from Example 1 is that in step S1, 60g of vitamin C and 4.8g of tea polyphenols (8% of the mass of vitamin C) are added to 240g of purified water and stirred at 30°C for 15min until homogeneous, resulting in 304.8g of aqueous core material internal phase and 64.8g of core material functional substances.
[0072] In step S2, the composite carrier consists of 40g gellan gum, 30g pea protein, and 15g colloidal microcrystalline cellulose, in a mass ratio of 40:30:15, totaling 85g. The colloidal microcrystalline cellulose accounts for 17.6% of the total mass of the composite carrier. Additionally, 12g of isomaltooligosaccharide is added as a pore-forming component (using the same mass ratio as the composite carrier, i.e., 12 parts). First, 40g of gellan gum is added to 1600g of purified water and stirred at 80℃ and 400r / min for 30min until completely dissolved. After cooling to 32℃, the pea protein, colloidal microcrystalline cellulose, and isomaltooligosaccharide are added, and stirring continues for 30min until uniformly dispersed, resulting in a composite carrier solution with a mass concentration of approximately 5.0% (85 / 1685=5.04%). Dissolving the gellan gum before adding the protein avoids excessive denaturation of the pea protein at 80℃, which could affect subsequent enzymatic cross-linking. The mass ratio of the core material functional substance to the composite carrier is 1:1.31.
[0073] In step S3, the microcapsule dispersion was sheared at 12000 r / min for 5 min, and the pH was adjusted to 4.2 at 32℃. The D[4,3] of the resulting microcapsule dispersion was 30.5 μm.
[0074] In step S4, the system was cooled to 24°C, and 40.0g of a 10% calcium lactate solution (containing 4.00g of calcium lactate pentahydrate, which, based on a calcium content of 13.0%, translates to 0.52g of calcium ions, or 1.3% of the gellan gum mass) was added. The mixture was stirred for 15 minutes. Based on a tetrasaccharide repeating unit molar mass of 648.6g / mol, gellan gum contains 1.54mmol of dissociable carboxyl groups per gram. Therefore, 40g of gellan gum contains 61.7mmol of dissociable carboxyl groups. The molar mass of calcium ions is 0.52 / 40.08 = 13.0mmol, the molar ratio of calcium ions to dissociable carboxyl groups is 0.210, and the molar fraction of free carboxyl groups in the shell is (61.7 - 2 × 13.0) / 61.7 × 100% = 57.9%. Therefore, since the content of dissociable carboxyl groups per unit mass of different pH-sensitive polysaccharides varies, the mass percentage dosage based on calcium ions must meet the requirements of a molar ratio of 0.10 to 0.25 and a free carboxyl molar fraction of 50% to 80%.
[0075] In step S4, the second stage, 6.00 g of transglutaminase (600 U, enzyme activity equivalent to 20 U / g of pea protein) was added within 8 min after the ionic cross-linking was completed. Simultaneously, the temperature was raised to 40℃ and reacted for 30 min, followed by enzyme inactivation at 72℃ for 4 min. The resulting microcapsules D[4,3] had a diameter of 29.0 μm, a shell thickness of 1.5 μm, a shell-to-thickness ratio of 1.5 / 29.0 = 0.052, and a radial protein network distribution gradient of 1.8.
[0076] In step S5, the cross-linked microcapsule suspension is concentrated in a vacuum film at 45°C and 5 kPa absolute pressure to a solid content of about 30%, yielding a suspension of about 576 g (of which about 173 g is non-volatile, including 64.8 g of core material functional material, 85 g of compound carrier, 12 g of isomaltooligosaccharide, 4.00 g of calcium lactate, 6.00 g of transglutaminase and about 1.0 g of citric acid). 200g of microcrystalline cellulose and 280g of lactose were mixed to obtain 480g of excipient mixture powder. The concentrated suspension was added in 5 batches using a slurry-intermediate drying method, with each batch containing approximately 115g (24.0% of the mass of the excipient mixture powder). After each batch was made into a soft mass and passed through a 24-mesh sieve, it was intermediately dried at an inlet air temperature of 60℃ for 15 minutes. The final drying was carried out for 40 minutes until the moisture content of the particles was no higher than 3.0%. The particles were then granulated and passed through a 20-mesh sieve to obtain approximately 653g of particles. 3.26g of magnesium stearate (0.5% of the particle mass) was added and mixed well. The mixture was then filled into No. 0 hard capsules, with each capsule containing 0.40g of vitamin C, to obtain vitamin C microcapsules. Each capsule contains approximately 37mg of vitamin C.
[0077] As determined by the methods of Test Examples 1 and 2, the capsule wall integrity rate of Example 6 was 93.5%, the product activity retention rate was 96.8%, the cumulative release rate in simulated gastric juice over 2 hours was 5.6%, and the cumulative release rate in simulated intestinal juice over 45 minutes was 95.1%, all meeting the performance requirements of this invention. This example demonstrates that the technical solution of this invention can still be implemented when the pH-sensitive polysaccharide is replaced with gellan gum, the modified cellulose is replaced with colloidal microcrystalline cellulose, the pore-forming component is replaced with isomaltooligosaccharide, the antioxidant is replaced with tea polyphenols, and the dosage form is changed to hard capsules.
[0078] Comparative Example 1 The difference from Example 1 is that the encapsulation and cross-linking treatment in steps S2 to S4 is not performed. Instead, 60g of vitamin C and 6g of soybean lecithin are directly added to a mixture of 200g of microcrystalline cellulose and 290g of lactose. Purified water is used as a binder. Tablets are prepared using the same number of additions (5 times) and single liquid ratio (approximately 20% of the mass of the excipient mixture) as in Example 1, as well as the same granulation, drying and tableting conditions.
[0079] Comparative Example 2 The difference from Example 1 is that a pre-prepared microcapsule powder was used for subsequent feeding. 40g of chitosan and 60g of maltodextrin (mass ratio 2:3) were dispersed in 1900g of a 1% citric acid aqueous solution to prepare a wall material solution. 60g of vitamin C and 6g of soybean lecithin were added, and the mixture was sheared and dispersed at 10000r / min for 5min. Then, it was spray-dried at an inlet air temperature of 185℃ and an outlet air temperature of 95℃ to obtain approximately 152g of microcapsule powder. The microcapsule powder was then wet-granulated, dried, and tableted according to the conditions of Comparative Example 1. The morphology of the rehydrated microcapsules after granulation is shown in the figure. Figure 2 (c) in the middle.
[0080] Comparative Example 3 The difference from Example 1 is that in step S4, only calcium lactate is added for ionic cross-linking (1.80 g of calcium ions, which is 4.0% of the mass of sodium alginate), and transglutaminase is not added; the shell layer only has an ionic cross-linking network. The surface morphology after granulation and drying is shown in the figure. Figure 3 (b) in the middle.
[0081] Comparative Example 4 The difference from Example 1 is that calcium lactate is not added in step S4, but only 5.25g of transglutaminase is added at 38°C for enzymatic covalent cross-linking for 40min. The shell layer has only a covalent cross-linking network and the free carboxyl molar fraction of the shell layer is 100%.
[0082] Comparative Example 5 The difference from Example 1 is that: the compound carrier does not contain sodium carboxymethyl cellulose, and the modified cellulose accounts for 0% of the total mass of the compound carrier, which is lower than the 5% to 20% range of the present invention; sodium alginate and soy protein isolate are still combined in a 45:35 ratio, and the total mass of the two is made up to 92g, that is, sodium alginate 51.75g and soy protein isolate 40.25g; the amount of calcium ions added is 4.0% of the mass of sodium alginate, that is, 2.07g; transglutaminase is added at 15U / g of soy protein isolate, that is, 6.04g.
[0083] Comparative Example 6 The difference from Example 1 is that the amount of sodium carboxymethyl cellulose is increased to 30g, while the amounts of sodium alginate and soy protein isolate remain unchanged. The total mass of the compound carrier is 110g, and sodium carboxymethyl cellulose accounts for 27.3% of the total mass of the compound carrier, which exceeds the range of 5% to 20% of the present invention. The mass ratio of the core material functional substance to the compound carrier is 1:1.67.
[0084] Comparative Example 7 The difference from Example 1 is that in step S4, 242.3g of a 10% calcium lactate solution (containing 24.23g of calcium lactate pentahydrate and 3.15g of calcium ions, which is 7.0% of the mass of sodium alginate) was added. The molar ratio of calcium ions to dissociable carboxyl groups was 0.346, which exceeds the range of 0.10–0.25 of this invention. The molar fraction of free carboxyl groups in the shell was (227.2 - 2 × 78.6) / 227.2 × 100% = 30.8%, which is lower than the range of 50%–80% of this invention. The remaining raw materials and process parameters are the same as in Example 1.
[0085] Comparative Example 8 The difference from Example 1 is that the cross-linking order is reversed in step S4. First, 5.25g of transglutaminase is added at 38°C and reacted for 40min. Then, the enzyme is inactivated by maintaining the temperature at 70°C for 5min. After cooling to 25°C, 138.5g of 10% calcium lactate solution (1.80g of calcium ions) is added and stirred for 15min to carry out ionic cross-linking. Because the ionic cross-linking network for shaping the primary capsule wall has not yet been formed before enzymatic cross-linking, the protein network is relatively dispersed in the bulk phase, the shell outline is diffuse, the apparent shell thickness is 2.6μm, the apparent shell thickness ratio is 0.068, and the radial protein network distribution gradient value is 1.05.
[0086] Comparative Example 9 The difference from Example 1 is that the segmented temperature control and sequential cross-linking were omitted in step S4. Instead, 138.5 g of a 10% calcium lactate solution (1.80 g of calcium ions) and 5.25 g of transglutaminase were added simultaneously at 38°C, and the reaction was carried out at 38°C for 40 min, followed by enzyme inactivation at 70°C for 5 min. The resulting microcapsule shell thickness was 2.0 μm, the shell-to-thickness ratio was 0.052, and the radial protein network distribution gradient value was 1.20.
[0087] Comparative Example 10 The difference from Example 1 is that the mass ratio of the core material functional substance to the compound carrier is 1:8, which exceeds the range of 1:1 to 1:4 of this invention. The compound carrier consists of 258.3g of sodium alginate, 200.9g of soy protein isolate, and 68.8g of sodium carboxymethyl cellulose (the mass ratio is still 45:35:12), totaling 528g, dissolved or dispersed in 10000g of purified water, with a compound carrier solution mass concentration of approximately 5.0%; the amount of calcium ions added is 4.0% of the mass of sodium alginate, i.e., 10.33g (79.5g of calcium lactate pentahydrate); transglutaminase is added at 15U / g of soy protein isolate, i.e., 30.13g. The resulting microcapsules D[4,3] have a diameter of 40.0μm, a shell thickness of 4.5μm, and a shell-to-thickness ratio of 0.113, which exceeds the range of 0.02 to 0.10 of this invention.
[0088] Comparative Example 11 The difference from Example 1 is that the mass ratio of the core material functional substance to the compound carrier is 1:0.5, which exceeds the range of 1:1 to 1:4 of this invention. The compound carrier consists of 16.1g of sodium alginate, 12.6g of soy protein isolate, and 4.3g of sodium carboxymethyl cellulose (the mass ratio is still 45:35:12), totaling 33g, dissolved or dispersed in 1500g of purified water, with a mass concentration of approximately 2.2% for the compound carrier solution. The amount of calcium ions added is 4.0% of the mass of sodium alginate, i.e., 0.644g (4.95g of calcium lactate pentahydrate). Glutamine transaminase is added at 15U / g of soy protein isolate, i.e., 1.89g. The resulting microcapsules D[4,3] have a diameter of 42.0μm, a shell thickness of 0.48μm, and a shell-to-thickness ratio of 0.011, which is lower than the range of 0.02 to 0.10 of this invention.
[0089] Test Example 1: Test of Capsule Wall Integrity and Processing Activity Retention Rate Samples were taken from each group of microcapsules after they were incorporated into the corresponding formulation process. Examples 1, 4, 5, and Comparative Examples 1 to 6 used samples after wet granulation and drying; Example 2 used the contents of soft capsules; and Example 3 used spray-dried granules. Samples were rehydrated with purified water at a mass ratio of 1:20 and dispersed by stirring at 200 rpm for 10 min. Multiple fields of view were randomly selected under a 400x optical microscope, and at least 300 microcapsules were counted cumulatively. Microcapsules with continuous wall contours, no through-cracks, and no significant leakage of core material were considered intact microcapsules. The integrity rate was calculated as "number of intact microcapsules / total number of counted microcapsules × 100%". Three batches of samples were prepared in parallel for each group, and the average value was taken. The finished product activity retention rate was calculated as "actual content of active ingredient in finished product / theoretical content of feed × 100%"; the active ingredient content per tablet, capsule, or bag mentioned in the examples refers to the theoretical content calculated based on the feed amount, and the actual content in the finished product is characterized by the finished product activity retention rate; the methods for determining the content of vitamin C, α-lipoic acid, and reduced glutathione are described in item 8 of the aforementioned "Detection and Characterization Methods". The test results are shown in Table 1 and... Figure 6 Surface morphology of double cross-linked microcapsules after granulation and drying. Figure 3 (a) Table 1 shows the test results of capsule wall integrity rate and viability retention rate for the examples and comparative examples:
[0090] As shown in Table 1, the capsule wall integrity rate of Examples 1 to 5 after the corresponding formulation processes was no less than 92%, and the activity retention rate of the finished product was no less than 95%. The activity retention rate of Comparative Example 1 (without encapsulation) was 72.5%, and the capsule wall integrity rate of Comparative Example 2 (pre-formulated microcapsule dry powder re-addition) was 61.3%, and the activity retention rate was 78.9%. When only ionic crosslinking or only covalent crosslinking was performed, the capsule wall integrity rate and activity retention rate were lower than those of the double crosslinking examples; Comparative Example 5 (without modified cellulose) also showed a significant decrease. This indicates that the ionic crosslinking network formed first can quickly shape the capsule wall, the protein covalent crosslinking network formed subsequently can improve the capsule wall connection strength, and the rigid skeleton of modified cellulose can share the stress of granulation shearing and drying shrinkage. The combined effect of these three factors helps to maintain the integrity of the capsule wall. Although Comparative Example 6 had a higher capsule wall integrity rate, its intestinal fluid release performance decreased, indicating that simply increasing the rigid skeleton cannot simultaneously ensure processing stability and release performance.
[0091] Test Example 2: In vitro simulated gastrointestinal release test The media were prepared and measured according to items 6 and 7 of the aforementioned "Detection and Characterization Methods". The release test target was the microcapsules in the cross-linked microcapsule suspension prepared in step S4 of each group. The suspension was directly added as a sample, and the sample amount was calculated to be equivalent to about 100 mg of active component. For samples with core material containing edible oil, 0.5% (w / v) of polysorbate 80 was added to both media to meet the leakage conditions. The microcapsules of each group were incubated in simulated gastric fluid at 37℃ and pH 1.2 for 2 h, and the cumulative release rate of the core material was measured. After the gastric fluid stage, the media was rapidly filtered through a 0.45 μm microporous membrane to collect the microcapsules and rinsed once with 10 mL of purified water. Within 2 min, the media, along with the collected microcapsules, was transferred into simulated intestinal fluid at 37℃, pH 6.8 and containing pancreatic enzymes. The volume of gastric fluid brought in with the filtrate was no more than 5 mL. The pH of the intestinal fluid after transfer was measured to be 6.8 ± 0.1. The cumulative release rate of the core material was measured at 45 min. The test results are shown in Table 2 and Figure 7 .
[0092] Table 2. Results of in vitro simulated gastrointestinal release tests for the examples and comparative examples:
[0093] As shown in Table 2, the cumulative release rates of Examples 1 to 5 in simulated gastric fluid were all no higher than 6.2% after 2 hours, and no lower than 91% after 45 minutes in simulated intestinal fluid. Comparative Examples 3 and 4, which only have a single cross-linked network, had cumulative release rates of 15.8% and 12.4% respectively in simulated gastric fluid, indicating that a single network is more prone to localized leakage in an acidic environment. Comparative Example 6, with excessive modified cellulose, had a cumulative release rate of only 71.5% in simulated intestinal fluid after 45 minutes, indicating that an excessively high proportion of rigid skeleton limits the swelling and dissociation of the shell in a neutral medium. Examples 4 and 5 contain trehalose, which dissolves in intestinal fluid to form microporous channels, increasing the cumulative release rate to over 95% after 45 minutes.
[0094] Test Example 3: Accelerated Stability Test The vitamin C microcapsules of Examples 1 and 5, the α-lipoic acid microcapsules of Example 2, and the tablets of Comparative Examples 1 and 2 were sealed in high-density polyethylene bottles (each bottle containing 1g of silica gel desiccant) and placed at 40±2℃ and 75±5% relative humidity for 3 months. Samples were taken monthly to determine the content of the active ingredients, and the retention rate of the active ingredients was calculated with the initial content as 100%. The test results are shown in Table 3 and... Figure 8 .
[0095] Table 3. Accelerated stability test results of the examples and comparative examples.
[0096] As shown in Table 3, the retention rates of active components in Examples 1, 2, and 5 after 3 months of accelerated storage were all no less than 95.7%, while those in Comparative Examples 1 and 2 decreased to 81.4% and 84.0%, respectively. The double cross-linked interpenetrating network shell and the modified cellulose rigid skeleton can reduce the transfer of water vapor and oxygen to the core material, and together with the antioxidants in the core material, inhibit thermo-oxidative degradation; the damage to the capsule wall that occurs during the redispersion and granulation of the pre-prepared microcapsule dry powder weakens its subsequent barrier ability.
[0097] Test Example 4: Characterization of Shell Structure Parameters According to items 1 to 5 of the aforementioned "Detection and Characterization Methods", the shell thickness, shell thickness ratio, free carboxyl molar fraction and radial protein network distribution gradient value of each group of cross-linked microcapsule suspensions were measured, and the results are shown in Table 4.
[0098] Table 4. Characterization results of shell structure parameters in the embodiments and comparative examples:
[0099] As shown in Table 4, the shell thickness ratios of Examples 1 to 6 were all 0.02–0.10, the free carboxyl molar fraction was all 50%–80%, and the radial protein network distribution gradient values were all 1.5–3.0. Comparative Example 4 did not contain calcium salts, so there were no calcium sites in the shell, and the free carboxyl molar fraction was 100%. Due to the lack of ionic cross-linking network to shape the primary capsule wall before enzymatic cross-linking, its radial protein network distribution gradient value was only 1.1, and the protein network was nearly uniformly distributed radially in the shell.
[0100] Test Example 5: Criticality Verification of Key Parameters To verify the relationship between the free carboxyl molar fraction, shell thickness ratio, and radial protein network distribution gradient value as defined in this invention and processing stability and release performance, Examples 1 and Comparative Examples 7 to 11 were measured according to the methods of Test Example 1 and Test Example 2, and the results are shown in Table 5.
[0101] Table 5. Criticality verification results of key parameters:
[0102] As shown in Table 5: (1) In Comparative Example 7, the amount of calcium ions was increased to 7.0% of the mass of sodium alginate, the molar ratio of calcium ions to dissociable carboxyl groups increased to 0.346, and the molar fraction of free carboxyl groups in the shell decreased to 30.8%. The integrity rate of the capsule wall increased to 96.2%, and the cumulative release rate in simulated gastric juice decreased to 2.4% after 2 hours, but the cumulative release rate after 45 minutes in simulated intestinal juice was only 66.8%. These results indicate that although increasing the degree of calcium ion crosslinking can strengthen the capsule wall and reduce release in gastric juice, the reduction of free carboxyl groups will limit the swelling and dissociation of the shell in intestinal juice. This invention, by retaining 50% to 80% of free carboxyl groups and supplementing the capsule wall strength with a protein covalent crosslinking network and a modified cellulose intercalation phase, can simultaneously take into account processing stability and intestinal juice release.
[0103] (2) In Comparative Example 8, the cross-linking order was reversed, with enzymatic covalent cross-linking performed first followed by ionic cross-linking. The radial protein network distribution gradient value decreased to 1.05, the shell outline became diffuse, the integrity rate of the capsule wall decreased to 76.2%, and the cumulative release rate of simulated gastric juice over 2 hours increased to 13.8%. In Comparative Example 9, calcium salt and transglutaminase were added simultaneously at the same temperature, and the segmented temperature control and sequential cross-linking were eliminated. The radial protein network distribution gradient value was 1.20, the integrity rate of the capsule wall was 82.4%, and the cumulative release rate of simulated gastric juice over 2 hours was 10.6%. The above results indicate that the sequence of low-temperature ionic cross-linking followed by high-temperature enzymatic covalent cross-linking and segmented temperature control is beneficial for forming a protein network that is relatively rich on the outside and relatively loose on the inside, and improves the integrity of the capsule wall and the protective performance in the stomach.
[0104] (3) The shell thickness ratio of Comparative Example 10 was 0.113, which is higher than the upper limit specified in this invention. Although its capsule wall integrity rate was 96.8%, the cumulative release rate after 45 minutes in simulated intestinal fluid was only 72.4%, indicating that an excessively thick shell layer would delay swelling and dissociation in intestinal fluid. The shell thickness ratio of Comparative Example 11 was 0.011, which is lower than the lower limit specified in this invention. Its capsule wall integrity rate was 68.5%, and the cumulative release rate of simulated gastric fluid after 2 hours was 22.3%, indicating that an excessively thin shell layer could not withstand the stress of granulation shearing and drying shrinkage. A shell thickness ratio of 0.02 to 0.10 is beneficial for simultaneously obtaining processing stability, gastric protection, and intestinal fluid release performance.
[0105] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Any equivalent substitutions, improvements, or modifications made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A heat-sensitive nutritional composition, characterized in that: The invention comprises core-shell structured microcapsules, the core-shell structured microcapsules comprising a core material and an interpenetrating network shell covering the core material, the core material comprising thermosensitive nutrient components and antioxidants; The interpenetrating network shell is formed by ionic crosslinking and enzymatic covalent crosslinking of a complex carrier. The complex carrier comprises, by weight, 30-60 parts of pH-sensitive polysaccharide, 20-50 parts of edible plant protein, and 5-20 parts of modified cellulose, and the mass of the modified cellulose is 5%-20% of the total mass of the pH-sensitive polysaccharide, edible plant protein, and modified cellulose. The pH-sensitive polysaccharide is partially cross-linked by calcium ions to form an ionic cross-linked network, and the edible plant protein is catalyzed by transglutaminase to form a covalent cross-linked network. The ionic cross-linked network and the covalent cross-linked network are interpenetrating each other, and the modified cellulose is fixed between the two networks by a non-covalent interpenetrating phase. The free carboxyl molar fraction of the pH-sensitive polysaccharide in the interpenetrating network shell is 50%–80%. The ratio of the thickness of the interpenetrating network shell to the volume average particle size D[4,3] of the core-shell structure microcapsules is 0.02 to 0.10; The ratio of the total mass of the thermosensitive nutrient component and the antioxidant to the total mass of the compound carrier is 1:1 to 1:4, and the volume average particle size D[4,3] of the core-shell structure microcapsules is 5 to 100 μm.
2. The thermosensitive nutritional composition according to claim 1, characterized in that: The covalent cross-linked network formed by the edible plant protein is distributed radially along the interpenetrating network shell in a pattern of relatively enriched outer side and relatively loose inner side. The distribution was characterized using analytical parallel samples with the same formulation and process as the microcapsules to be tested. The mass ratio of fluorescein isothiocyanate-labeled edible plant protein to unlabeled edible plant protein in the analytical parallel samples was 1:
19. When confocal imaging was performed on the equatorial plane of the microcapsules of the analytical parallel samples, the ratio of the average fluorescence intensity of the labeled protein in the outer half-thickness region to the inner half-thickness region of the shell was 1.5 to 3.
0.
3. The thermosensitive nutritional composition according to claim 1, characterized in that: The ionic cross-linking network is formed by cross-linking calcium ions provided by food-grade calcium salt with the pH-sensitive polysaccharide. The food-grade calcium salt is selected from one or more of calcium lactate, calcium chloride, and calcium gluconate. The amount of calcium ions used is 1.2% to 5.0% of the mass of the pH-sensitive polysaccharide, and the molar ratio of calcium ions to the dissociable carboxyl groups in the pH-sensitive polysaccharide is 0.10 to 0.
25. The covalent cross-linked network is formed by the formation of ε-(γ-glutamyl)-lysine isopeptide bonds between the edible plant protein molecules catalyzed by transglutaminase, and the amount of transglutaminase used is 5-30 U per gram of edible plant protein.
4. The thermosensitive nutritional composition according to claim 3, characterized in that: The pH-sensitive polysaccharide is selected from one or more of sodium alginate, low-ester pectin, and gellan gum, wherein the degree of esterification of the low-ester pectin is not higher than 45%; the edible plant protein is selected from one or two of soy protein isolate and pea protein; the modified cellulose is selected from one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, and colloidal microcrystalline cellulose.
5. The thermosensitive nutritional composition according to claim 4, characterized in that: The heat-sensitive nutrient component is selected from one or more of vitamin C and its salts or esters, B vitamins, vitamin A, vitamin D, vitamin E, alpha-lipoic acid, reduced glutathione, collagen peptides, soybean peptides, coenzyme Q10, lutein, and lycopene; wherein, water-soluble heat-sensitive nutrient components are dispersed in an aqueous medium to form the inner phase of the core material, and fat-soluble heat-sensitive nutrient components are dispersed in edible oils to form the inner phase of the core material. The antioxidant is selected from one or more of lecithin, vitamin E succinate, ascorbyl palmitate, rosemary extract and tea polyphenols, and its dosage is 2% to 15% of the mass of the heat-sensitive nutrient component.
6. The thermosensitive nutritional composition according to claim 5, characterized in that: The interpenetrating network shell contains a pore-forming component, which is trehalose and / or isomaltooligosaccharide, and its mass is 5% to 15% of the total mass of the pH-sensitive polysaccharide, edible plant protein and modified cellulose. The pore-forming component fills the network gaps of the interpenetrating network shell in a dry state and dissolves in a medium with pH 6.8 to form microporous channels.
7. The thermosensitive nutritional composition according to claim 6, characterized in that: The outer surface of the core-shell structured microcapsule is coated with a hydrophobic anti-adhesion layer composed of zein particles, the average particle size of which is 100-400 nm, and the amount of which is 3%-10% of the total mass of the pH-sensitive polysaccharide, edible plant protein and modified cellulose.
8. The thermosensitive nutritional composition according to claim 1, characterized in that: The modified cellulose does not participate in the covalent crosslinking catalyzed by the transglutaminase and exists as a non-covalent interpenetrating phase in the interpenetrating network shell; the modified cellulose is water-soluble modified cellulose or colloidal microcrystalline cellulose, the viscosity of the water-soluble modified cellulose measured at 20°C in a 1% (w / w) aqueous solution is not less than 500 mPa·s, and the average particle size of the colloidal microcrystalline cellulose is not greater than 0.5 μm.
9. The thermosensitive nutritional composition according to claim 1, characterized in that: When measured using the paddle method under conditions of a medium volume of 900 mL, a temperature of 37 ± 0.5 °C, and a rotation speed of 100 r / min, the cumulative release rate of the core material of the thermosensitive nutritional composition after incubation in simulated gastric fluid at pH 1.2 for 2 h was not higher than 8%, and the cumulative release rate of the core material after transferring the core-shell structure microcapsules into simulated intestinal fluid at pH 6.8 for 45 min was not lower than 90%.
10. A stabilization process for the heat-sensitive nutrient composition according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1, dispersing heat-sensitive nutrients and antioxidants in an aqueous medium or edible oil to obtain the inner phase of the core material; S2, 30-60 parts by weight of pH-sensitive polysaccharide, 20-50 parts by weight of edible plant protein and 5-20 parts by weight of modified cellulose are dispersed in water, wherein the mass of modified cellulose is 5%-20% of the total mass of the three components, to obtain a compound carrier solution with a mass concentration of 2%-8%. S3, according to the total mass ratio of the thermosensitive nutrient components and antioxidant to the total mass ratio of the pH-sensitive polysaccharide, edible plant protein and modified cellulose of 1:1 to 1:4, the inner phase of the core material is added to the compound carrier solution, and dispersed using a shear rate of 8000 to 15000 r / min or a homogenization pressure of 20 to 40 MPa. The pH of the system is adjusted to 3.5 to 4.5 at 25 to 40 °C, so that the edible plant protein and pH-sensitive polysaccharide are re-aggregated on the periphery of the core material dispersion micro-region to form the primary capsule wall, and a primary microcapsule dispersion with a volume average particle size D[4,3] of 5 to 100 μm is obtained. S4, Sequential cross-linking and curing: First, add food-grade calcium salt at 20-30℃ for ionic cross-linking. The amount of calcium ions added is 1.2% to 5.0% of the mass of the pH-sensitive polysaccharide, and the molar ratio of calcium ions to the dissociable carboxyl groups in the pH-sensitive polysaccharide is 0.10 to 0.
25. Stir for 10 to 20 minutes. Within 5–20 minutes after the completion of the ionic cross-linking, transglutaminase is added at an enzyme activity of 5–30 U per gram of the edible plant protein, and the system is heated to 30–45°C and reacted for 20–60 minutes. The temperature of the enzymatic covalent cross-linking is higher than that of the ionic cross-linking. Subsequently, the enzyme is inactivated by maintaining the temperature at 65–75°C for 3–10 minutes to obtain the cross-linked microcapsule suspension. Through the sequential cross-linking and curing, the free carboxyl molar fraction of the pH-sensitive polysaccharide in the interpenetrating network shell is 50% to 80%, and the covalent cross-linking network formed by the edible plant protein is distributed radially along the shell with a relatively rich outer side and a relatively loose inner side. In preparing the thermosensitive nutritional composition according to claim 6, trehalose and / or isomaltooligosaccharide are added in step S2, wherein the mass of trehalose and / or isomaltooligosaccharide is 5% to 15% of the total mass of the pH-sensitive polysaccharide, edible plant protein and modified cellulose; In preparing the thermosensitive nutritional composition according to claim 7, after enzyme inactivation, zein particles prepared by edible ethanol antisolvent method and ethanol removed are added. The amount of zein particles added is 3% to 10% of the total mass of the pH-sensitive polysaccharide, edible plant protein and modified cellulose, and the zein particles are adsorbed on the outer surface of the core-shell structure microcapsule. S5, the cross-linked microcapsule suspension is directly used as a liquid intermediate material in the wet granulation process, soft capsule filling process or spray drying process without microcapsule separation, washing and pre-drying. Alternatively, vacuum thin-film concentration can be carried out at a temperature not exceeding 45°C until the solid content reaches 15% to 35%, and then the wet granulation process, soft capsule filling process, or spray drying process can be initiated.
Citation Information
Patent Citations
B-complex crystal vitamin microcapsule and method for preparing microcapsules by utilizing spray drying method
CN102106480A
A kind of highly stable lactic acid bacteria microcapsules and its preparation method and application
CN104313005B